Exploring Acid-Base Imbalance in Liver Cirrhosis: Diagnostic and Therapeutic Perspectives - Usman, Muhammad; Muhammad, Syed Akhter; Abdul Malik; Naseer, Muhammad; Azam, Muhammad; Mohkumuddin, Syed (Indus Journal of Bioscience Research, 2025)
Background: liver cirrhosis Patients experience disturbances in their body acid-base balance which reflects disease of the liver and affect the whole body. Possible imbalances can be either metabolic alkalosis, respiratory alkalosis or high anion gap metabolic acidosis and each can provide valuable diagnostic and outcome insights. Objectives: To explore the processes, patterns and clinical outcomes of acid-base disorders in patients with cirrhosis and to suggest relevant diagnostic and treatment methods. Study Design: A Cross-Sectional Study. Place and Duration of study: From July 2024 to December 2024 Gastroenterology Department, Sandeman Provincial Hospital / Bolan Medical College / Hospital, Quetta. Methods: This cross-sectional study conducted at a tertiary Hospital between July 2024 to December 2024. We obtained the data from cirrhotic patients who had blood analyzed in an arterial blood gas test. Results: 94 cirrhotic patients investigated (mean age: 54.7 ± 9.6) years), 82.9% had acid-base disorders. A typical finding in our cohort was respiratory alkalosis which was seen in 46.8% of all patients and mainly related to hepatic encephalopathy or portosystemic shunting. In 17.0% of these patients, metabolic alkalosis took place, commonly seen in those who use a lot of diuretics and lose stomach fluids through vomiting. The majority of cases of high anion gap metabolic acidosis (11.7%) were found in patients with advanced liver failure, sepsis or trouble with kidney function 4% of the cases were mixed acid-base disorders. Marked hypoalbuminemia was found in nearly all cases (88%) which meant that albumin-corrected anion gap was used to accurately understand metabolic acidosis and enhance diagnostic precision. Conclusion: Irregular acid-base levels are typical in cirrhosis and often occur together. Correctly uncovering liver and kidney problems and using management based on these issues is necessary to improve these patients’ outcomes.